A Family of LIM-Only Transcriptional Coactivators: Tissue-Specific Expression and Selective Activation of CREB and CREM - Fimia, Gian Maria (American Society for Microbiology, 2000)
Transcription factors of the CREB family control the expression of a large number of genes in response to various signaling pathways. Regulation mediated by members of the CREB family has been linked to various physiological functions. Classically, activation by CREB is known to occur upon phosphorylation at an essential regulatory site (Ser133 in CREB) and the subsequent interaction with the ubiquitous coactivator CREB-binding protein (CBP). However, the mechanism by which selectivity is achieved in the identification of target genes, as well as the routes adopted to ensure tissue-specific activation, remains unrecognized. We have recently described the first tissue-specific coactivator of CREB family transcription factors, ACT (activator of CREM in testis). ACT is a LIM-only protein which associates with CREM in male germ cells and provides an activation function which is independent of phosphorylation and CBP. Here we characterize a family of LIM-only proteins which share common structural organization with ACT. These are referred to as four-and-a-half-LIM-domain (FHL) proteins and display tissue-specific and developmentally regulated expression. FHL proteins display different degrees of intrinsic activation potential. They provide powerful activation function to both CREB and CREM when coexpressed either in yeast or in mammalian cells, specific combinations eliciting selective activation. Deletion analysis of the ACT protein shows that the activation function depends on specific arrangements of the LIM domains, which are essential for both transactivation and interaction properties. This study uncovers the existence of a family of tissue-specific coactivators that operate through novel, CBP-independent routes to elicit transcriptional activation by CREB and CREM. The future identification of additional partners of FHL proteins is likely to reveal unappreciated aspects of tissue-specific transcriptional regulation.